2016
DOI: 10.1038/cddis.2016.191
|View full text |Cite
|
Sign up to set email alerts
|

Does murine spermatogenesis require WNT signalling? A lesson from Gpr177 conditional knockout mouse models

Abstract: Wingless-related MMTV integration site (WNT) proteins and several other components of the WNT signalling pathway are expressed in the murine testes. However, mice mutant for WNT signalling effector β-catenin using different Cre drivers have phenotypes that are inconsistent with each other. The complexity and overlapping expression of WNT signalling cascades have prevented researchers from dissecting their function in spermatogenesis. Depletion of the Gpr177 gene (the mouse orthologue of Drosophila Wntless), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Genetic alternations and epigenetic regulations are two major mechanisms controlling the spatial and temporal expression of miRNAs 27 . Analysis of high-resolution copy-number variation (CNV) datasets from The Cancer Genome Atlas (TCGA) demonstrated that deletions (approximately 8%) and amplifications (approximately 1.7%) of precursor miR-125b (miR-125b1 and miR-125b2) were barely detected in 156 TGCT samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic alternations and epigenetic regulations are two major mechanisms controlling the spatial and temporal expression of miRNAs 27 . Analysis of high-resolution copy-number variation (CNV) datasets from The Cancer Genome Atlas (TCGA) demonstrated that deletions (approximately 8%) and amplifications (approximately 1.7%) of precursor miR-125b (miR-125b1 and miR-125b2) were barely detected in 156 TGCT samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Five‐micron paraffin‐embedded sections were cut for staining. Haematoxylin and eosin stain, immunofluorescence (IF), and immunohistochemistry (IHC) were performed as previously described in our laboratory (Chen, Tang, Cheng, Hao et al, 2016; Wen et al, 2016). The primary antibodies were listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…34 Conditional knockout of Wls in a specific cell type in other organs has shown that the lack of Wls blocks Wnt secretion from the producing cells and abolishes Wnt functions in the responding cells. [35][36][37][38][39] However, a similar strategy to block Wnt secretion via conditional ablation of Wls in the kidney has not been reported.…”
mentioning
confidence: 99%